Expression of mutant exon 1 huntingtin fragments in human neural stem cells and neurons causes inclusion formation and mitochondrial dysfunction. Issue 6 (23rd April 2020) - Ghosh, Rhia; Wood‐Kaczmar, Alison; Dobson, Lucianne; Smith, Edward J.; Sirinathsinghji, Eva C.; Kriston‐Vizi, Janos; Hargreaves, Iain P.; Heaton, Robert; Herrmann, Frank; Abramov, Andrey Y.; Lam, Amanda J.; Heales, Simon J.; et al.
Abstract: Robust cellular models are key in determining pathological mechanisms that lead to neurotoxicity in Huntington's disease (HD) and for high throughput pre‐clinical screening of potential therapeutic compounds. Such models exist but mostly comprise non‐human or non‐neuronal cells that may not recapitulate the correct biochemical milieu involved in pathology. We have developed a new human neuronal cell model of HD, using neural stem cells (ReNcell VM NSCs) stably transduced to express exon 1 huntingtin (HTT) fragments with variable length polyglutamine (polyQ) tracts. Using a system with matched expression levels of exon 1 HTT fragments, we investigated the effect of increasing polyQ repeat length on HTT inclusion formation, location, neuronal survival, and mitochondrial function with a view to creating an in vitro screening platform for therapeutic screening. We found that expression of exon 1 HTT fragments with longer polyQ tracts led to the formation of intra‐nuclear inclusions in a polyQ length‐dependent manner during neurogenesis. There was no overt effect on neuronal viability, but defects of mitochondrial function were found in the pathogenic lines. Thus, we have a human neuronal cell model of HD that may recapitulate some of the earliest stages of HD pathogenesis, namely inclusion formation and mitochondrial dysfunction.